CORPORATE GOVERNANCE AND RISK MANAGEMENT: A Study of Board Structure in Indonesian and Singapore Companies - Muhammad Muhammad; Dwi Narullia (Universitas Halu Oleo, 2021)
This study aims to determine the effect of the board structure on business risk management. One indicator that can show the implementation of risk management is risk disclosure by the company. This study uses a quantitative approach with the research population being companies in Indonesia and Singapore included in the ASEAN Stars 2015 – 2018. Furthermore, this study uses a regression analysis technique to examine the effect of the board structure on corporate risk management. The results of this study indicate that although the structure of the board of companies included in ASEAN STARS in Indonesia and Singapore has differences, the results of the analysis of the two are not much different. This study shows that an independent board of commissioners and the frequency of meetings have a significant effect on the company's risk management. Otherwise, the composition of the female board of commissioners is proven not to affect the risk management. Overall, the results also show an increase in corporate governance activities and an increase in risk management activities. The results of this study can be used as input for potential investors to evaluate quantitative information, and other qualitative information such as the role of the board of commissioners and risk disclosure can be useful in decision making.